Improved dielectric behaviour of graphene oxide-multiwalled carbon nanotube nanocomposite. (February 2018) - Kavinkumar, T.; Manivannan, S.
Abstract: We have prepared graphene oxide (GO)-multiwalled carbon nanotube (MWCNT) composite film through vacuum filtration method. In this work, we carried out the dielectric behaviour of GO-MWCNT composite film in the frequency range of 100 Hz to 1 MHz and temperature range of 30–200 °C. The GO-MWCNT composite film showed significantly higher dielectric constant as 6021 than the GO (5031) which was even very high compared to conventional dielectric materials. The enhancement of dielectric constant is attributed to the strong interaction between sp 2 MWCNT fillers and sp 3 GO matrix as well as the formation of microcapacitors by highly conductive MWCNT segregated by GO sheets. Furthermore, we found interesting transition between semiconductor to conductor was attained at 165 °C. It is suggested that the temperature dependent transition of electrical properties of GO-MWCNT composite film is closely related with the ion mobility, removal of water molecules and reduction of GO in the composite. The effect of interfacial polarization and relaxation process were studied. The redox peak current has increased significantly for the GO-MWCNT composite electrode than the GO and MWCNT where the highly conducting MWCNT provide the necessary conduction pathways on the electrode surface. These flexible, high dielectric constant nanocomposites are potential flexible dielectric materials for use in high frequency capacitors and in electronic devices. Highlights: GO and GO-MWCNT composite films prepared through vacuum filtration method. GO-MWCNT composite showed significantly higher ε′ than GO. Transition from semiconductor to conductor was attained at 165 °C for GO-MWCNT composite. Electrical properties of composite is related with the ion mobility, removal of water molecules and reduction of GO in the composite.